Healthcare Providers' Attitudes, Knowledge, and Practice Behaviors for Educating Patients About Advance Directives: A National Survey. (May 2019) - Nedjat-Haiem, Frances R.; Cadet, Tamara J.; Amatya, Anup; Mishra, Shiraz I.
Background: Advance care planning for end-of-life care emerged in the mid-1970's to address the need for tools, such as the advance directive (AD) legal document, to guide medical decision-making among seriously ill patients, their families, and healthcare providers. Objective: Study aims examine providers' perspectives on AD education that involve examining (1) a range of attitudes about educating patients, (2) whether prior knowledge was associated with practice behaviors in educating patients, and (3) specific factors among healthcare providers such as characteristics of work setting, knowledge, attitudes, and behaviors that may influence AD education and documentation. Design: To examine providers' views, we conducted a cross-sectional, online survey questionnaire of healthcare providers using social media outreach methods for recruitment. Methods: This study used a cross-sectional survey design to examine the proposed aims. Healthcare providers, recruited through a broad approach using snowball methods, were invited to participate in an online survey. Logistic regression analyses were used to examine providers' views toward AD education. Results: Of 520 participants, findings indicate that most healthcare providers said that they were knowledgeable about AD education. They also viewed providing education as beneficial to their practice. These findings suggest that having a positive attitude toward AD education and experiencing less organizational barriers indicate a higher likelihood that providers will educate patients regarding ADs. Conclusion: Various disciplines are represented in this study, which indicates that attitudes and knowledge influence AD discussions. The importance of AD discussions initiated by healthcare providers is critical to providing optimal patient-centered care.